2019
DOI: 10.1155/2019/7018937
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Angle κ and Higher-Order Aberrations on Visual Quality Employing Two Diffractive Trifocal IOLs

Abstract: Prospective, randomized, comparative, and controlled study to estimate the association between angle κ distance and higher-order aberrations (HOAs) with postoperative visual acuity after presbyopia-correcting IOL implantation. Forty-three eyes from 43 patients were included and randomly assigned in two groups for either AT LISA tri 839MP or Acrysof IQ PanOptix IOL implantation. The OPD-Scan III analyzer was utilized to assess the angle κ distance and higher-order aberration (HOAs). Twenty-three eyes were in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“… 10–13 As shown in Table 2 , the manifest refraction and visual acuity were not statistically significantly different by AK group. These findings appear to corroborate the results reported by Garzón et al 8 and Velasco-Barona et al, 9 though the first study related to a different trifocal IOL. The refractive and acuity results also appear consistent with the results from Qi et al, 7 where visual disturbances, but not refraction and acuity, appeared related to higher AK values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 10–13 As shown in Table 2 , the manifest refraction and visual acuity were not statistically significantly different by AK group. These findings appear to corroborate the results reported by Garzón et al 8 and Velasco-Barona et al, 9 though the first study related to a different trifocal IOL. The refractive and acuity results also appear consistent with the results from Qi et al, 7 where visual disturbances, but not refraction and acuity, appeared related to higher AK values.…”
Section: Discussionsupporting
confidence: 92%
“… 7 Other studies involving trifocal IOLs found no correlations between angle kappa and any measures of vision or visual quality. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if a diffractive mIOL is decentered from the visual axis, it could result in decreased vision, inducing higher-order aberrations and photic phenomena, including reduced contrast sensitivity, glare, and halos. [6][7][8][9] In addition, the lens tends to allocate on the center of the capsular bag, which is more closely related to the center of the limbus. Therefore, it is necessary to know in advance whether the visual axis and the center of the WTW diameter of the patient are misaligned.…”
mentioning
confidence: 99%
“…Corneal topographic systems have been used to evaluate K . [ 2 35 36 37 ] Topographers estimate K by measuring the distance between the pupil centre and the first Purkinje image of an axial target (the bright corneal reflex) when the eye is in the primary position of gaze. It is assumed that the intercept (a) between the visual axis and the anterior corneal surface coincides with the location of this bright corneal reflex and (b) of the pupillary axis striking the anterior corneal surface coincides with the pupil center.…”
Section: Methodsmentioning
confidence: 99%